2022
DOI: 10.7759/cureus.22087
|View full text |Cite
|
Sign up to set email alerts
|

Severity of COVID-19 Infection Using Chest Computed Tomography Severity Score Index Among Vaccinated and Unvaccinated COVID-19-Positive Healthcare Workers: An Analytical Cross-Sectional Study

Abstract: Introduction: Coronavirus disease 2019 (COVID-19) vaccines protect against severe illness. However, data on post-vaccination COVID-19 breakthrough infections are limited.Methods: An analytical cross-sectional study was conducted from May 2021 to July 2021 among 2043 COVID-19-positive healthcare workers who were divided into a vaccinated group (n=1010) and an unvaccinated group (n=1033). A pre-tested questionnaire was circulated among the healthcare workers using Google Forms. Chest computed tomography (CT) sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
3
7
0
Order By: Relevance
“…These observations were corresponding to the results obtained from our study. Minimal clinical severity as depicted by the lower CT-SSs among the vaccinated people as compared to the unvaccinated population was also reported by other studies [ 23 - 25 ].…”
Section: Discussionsupporting
confidence: 82%
“…These observations were corresponding to the results obtained from our study. Minimal clinical severity as depicted by the lower CT-SSs among the vaccinated people as compared to the unvaccinated population was also reported by other studies [ 23 - 25 ].…”
Section: Discussionsupporting
confidence: 82%
“…This result was concordant with Lee et al, who did not find any difference in lung involvement when SARS-CoV-2 infection developed into interstitial pneumonia [21]. Other studies [19,20,29] reported a significantly greater extent of pulmonary disease in the incompletely vaccinated and non-vaccinated patients compared to the completely vaccinated group, probably due to a different method for assessing lung involvement. In fact, Verma, Joshi, and Ravindra [19,20,29] used the 5-point scale of CT severity score compared to the binary score (< 25% vs. ≥ 25%) proposed by Lee [21] and our study, which did not consider any difference between the highest lung involvement volumes.…”
Section: Discussionsupporting
confidence: 88%
“…In the study of Mahajan et al [ 16 ], where they evaluated vaccinated and unvaccinated patients with a positive SARS-CoV-2 PCR test, they found that the CT-SS of vaccinated people was mild-moderate, while unvaccinated individuals were moderate-severe. Again, in the studies conducted by Russo et al [ 4 ], Ravindra et al [ 5 ], Fatima et al [ 6 ], and Yavuz et al [ 17 ], when the CT SS of vaccinated and unvaccinated patients were compared, it was shown that vaccinated patients had milder pulmonary involvement. In our study, it was shown that unvaccinated individuals had moderate-severe lung involvement, and patients who received two doses of CoronaVac or two doses of BioNTech or three doses of vaccine had moderate lung involvement.…”
Section: Discussionmentioning
confidence: 99%